2015
DOI: 10.1038/ejcn.2015.122
|View full text |Cite
|
Sign up to set email alerts
|

Index-based dietary patterns and risk of lung cancer in the NIH–AARP diet and health study

Abstract: Although smoking is the factor most strongly associated with lung cancer, this study adds to a growing body of evidence that diet may have a modest role in reducing lung cancer risk, especially among former smokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 35 publications
5
48
1
2
Order By: Relevance
“…This observation was consistent with the findings from previous dietary pattern studies on lung cancer that the beneficial effects of dietary patterns characterized by high consumption of fruits or vegetables were only evident in current or former smokers456910. Smoking causes lung cancer in part through its pro-oxidant properties31.…”
Section: Discussionsupporting
confidence: 91%
“…This observation was consistent with the findings from previous dietary pattern studies on lung cancer that the beneficial effects of dietary patterns characterized by high consumption of fruits or vegetables were only evident in current or former smokers456910. Smoking causes lung cancer in part through its pro-oxidant properties31.…”
Section: Discussionsupporting
confidence: 91%
“…In fact, one study showed that a "healthy eating" pattern that included vegetables, fruits, and low-fat foods was associated with a significant reduction in lung cancer risk among those who never smoked (33). Assessment of diet quality in the NIH-AARP Diet and Health study (N = 460,770) by scoring compliance with any of four common indices (Healthy Eating Index-2010, Alternative Healthy Eating Index-2010, alternative Mediterranean Diet score, and DASH Diet) yielded very similar results (34). Each type of diet offered similar reductions in risk; high dietary adherence to any of the four diet plans was associated with a 14-17% reduction in lung cancer risk (34).…”
Section: Dietary Patterns and Lung Cancer Riskmentioning
confidence: 86%
“…Assessment of diet quality in the NIH-AARP Diet and Health study (N = 460,770) by scoring compliance with any of four common indices (Healthy Eating Index-2010, Alternative Healthy Eating Index-2010, alternative Mediterranean Diet score, and DASH Diet) yielded very similar results (34). Each type of diet offered similar reductions in risk; high dietary adherence to any of the four diet plans was associated with a 14-17% reduction in lung cancer risk (34). Higher consumption of whole grains was among the individual components that were significantly inversely associated with lung cancer risk.…”
Section: Dietary Patterns and Lung Cancer Riskmentioning
confidence: 97%
“…1 There is growing interest in the development, estimation, and application of dietary pattern indices because of the relation between diet and chronic diseases [2][3][4][5] and mortality risk. 6 From a surveillance perspective, some dietary pattern indices are useful in determining how well populations meet national dietary recom mendations.…”
Section: Introductionmentioning
confidence: 99%